Understanding violence in medieval London: an examination of the skeletal evidence - Krakowka, K (2015)
It is often presumed that the medieval period was an exceptionally violent one. But, previously, this idea has predominately been based on historical evidence of violence. As this data is subject to numerous biases based on past perception of what connoted criminally violent behaviour, this assumption of excessive medieval violence can be called into question. This study attempts to rectify this problem by adding evidence of violence from the skeletal record, helping to create a more well-rounded picture of medieval violence. In total, data from over 6,000 skeletons, representing six different sites from medieval London, were analysed for evidence of violence-related injuries. The skeletal evidence was then interpreted using an approach that integrates both the historical evidence and cultural patterns of violence. The overall findings suggest that violence was prominent and affected all aspects of medieval London society, but how that violence was characterised depended on an individual’s sex, age, social status, and century of life.